IMPACT OF THE TELOK MELANO-SEMATAN PAN-BORNEO HIGHWAY ON THE HOMESTAY SECTOR IN TELOK MELANO,SARAWAK - Dilah, Tuah; Chong, Shin; Muhammad Jazlan, Ahmad Khiri (Seybold Publication, 2022)
Through both library and field research, this study investigates the impact of the Pan Borneo Highway Telok Melano-Sematan route on the Homestay service at Telok Melano, Lundu, Sarawak (Malaysia). A total of ten informants were interviewed, including the village chief and the homestay owners. The findings show the Pan Borneo highway's Telok Melano-Sematan section had a positive impact on the Telok Melano homestay program. Among the visible effects are increase in visitor arrivals, an increase in registered homestays, and an increase in the economic impact of ecotourism. Homestays are estimated to grow in numbers in the upcoming years, particularly with the installation of public facilities. This study is notably important in documenting the preliminary impact of the Pan Borneo highway construction on the local economy.